An application of growth diagnostics on the growth of firms: With evidence from Kosovo firms - Fadil Sahiti; Helen Lawton Smith (Journal of Innovation and Entrepreneurship, 2017)
This paper provides evidence on the impact of the business environment on the growth of firms in less-developed countries, with evidence from Kosovo firms. The theoretical perspective used is growth diagnostics. The data used to test the hypotheses were obtained from two different sources: international surveys and a manager survey dataset. The findings show that the business environment in Kosovo provides little incentive for firm growth. Further, empirical evidence shows that the business environment in Kosovo is characterised by low appropriability, with a high cost of capital, and in which complementary factors in the form of human capital are scarce.
Keywords: 650; Public goods; Constraints on growth; Infrastructure; Finance; Institutions; Firm-level data